OPTIMASI PENGGUNAAN FAKTOR EKSPOSI PADA PEMERIKSAAN BLASS NIER OVERZICHT (BNO) PADA PASIEN DENGAN BERAT BADAN 60-70KG - Rifa Afifah; Widya Mufida; Amril Mukmin (Journal of Innovation Research and Knowledge, 2025)
Background: The abdomen is a body part frequently examined through radiography to diagnose conditions such as acute abdomen, meteorism, or ileus. Proper exposure factor settings, particularly for patients weighing 60–70 kg, are crucial for obtaining high-quality diagnostic images while minimizing radiation doses. This study aims to analyze the optimization of exposure factor usage in abdominal radiography for patients weighing 60–70 kg at Sunan Kudus Islamic Hospital. Method: This research employed a descriptive qualitative method with a case study approach. Data collection was conducted in May 2025 at the Radiology Installation of Sunan Kudus Islamic Hospital. The sample consisted of three patients undergoing abdominal examinations. Data were gathered through observations, interviews with one radiology specialist and three radiographers, as well as documentation of projections. Data were analyzed through reduction and narrative presentation based on theoretical references for conclusions. Result: The examinations were performed with AP Supine, semi-sitting, and Left Lateral Decubitus (LLD) projections using exposure settings of 75–80 kV and 20–25 mAs. The resulting images displayed clear anatomical structures such as lumbar vertebrae, pelvic collar, and both large and small intestines, without significant noise. The radiographs were able to detect conditions such as obstructive ileus, pneumoperitoneum, and meteorism with localized ileus in the mid-abdomen. All patients received high- quality images without the risk of excessive radiation. Conclusion: The exposure settings of 75–80 kV and 20–25 mAs are effective for patients weighing 60-70kg. It is recommended to establish specific Standard Operating Procedures (SOP) regarding exposure factors for patients within this weight range at the Radiology Installation of Sunan Kudus Islamic Hospital